The effects of Clitoria Ternatea Linn (Butterfly Pea Flower) on angiogenesis using cam assay - Almoguera, Clarisa B.; Borela, Kassandra Mae E.; Casim, Francine N.; Cordenete, Jacinth V.; Rivera, Salvador III P. (b)
Clitoria ternatea Linn, an edible flower from the Fabaceae family, has shown potential benefits for managing diabetes, a condition marked by uncontrolled blood sugar levels. Diabetes is one of the diseases being treated by the flower. This study examined the antidiabetic activity of crude petal extracts from Clitoria ternatea Linn, using a Chorioallantoic Membrane (CAM) assay on 10-day-old duck embryos. A total of 535 g of dried petals were extracted with 95% methanol, yielding four concentrations: 80%, 50%, 30%6, and 10%. These were administered to duck embryos, while a Glibenclamide solution served as a positive control, and an untreated group served as a placebo. To induce hyperglycemia, the embryos received 1 mL of Alloxan Monohydrate and were incubated for 8 days. Following incubation, the CAM of each egg was harvested, and the length and number of blood vessels was counted meticulously. The study{92}s results were promising, with the extracts showing significant anti-diabetic effects (p-value of 0.0186 via ANOVA). A noticeable reduction in collaterals indicated effective absorption and inhibition of vascular growth, likely due to phenolic compounds such as flavonoids, kaempferol, quercetin, myricetin, glycosides, and anthocyanins. Following further analysis, the concentration of 30% is the appropriate amount to achieve the desired therapeutic effect demonstrating the potential of the butterfly pea flower as a natural antidiabetic agent. However, further research is needed to understand its mechanism of action and to validate these findings in clinical trials. The results contribute to the growing body of research exploring natural remedies for diabetes management.
Undergraduate thesis.
Keywords: Blood vessels; Anthocyanins; Flavonoids; Alloxan Monohydrate; Hyperglycemia; Blood sugar